Розсіювання енергії при коливаннях матеріалами з неоднорідними механічними властивостями або прямі і обернені задачі при розрахунку коливань шаруватих структур - Мозговий, О. В. (ООО «Компания «Индустриальные технологии», 2014)
Розглянута теоретично – експериментальна методика дослідження коливань шаруватих стержнів залежно від модулів пружності, форм і декрементів коливань кожного шару. Представлені результати вирішення оберненої задачі визначення вхідних параметрів і технологічних режимів при заданих експериментальних характеристиках готового виробу. Визначено характер впливу модуля пружності поверхневого шару на параметри розсіювання механічної енергії однорідного матеріалу з різними механічними характеристиками. Purpose. On the basis of theoretical and experimental methodologies for evaluating the mechanical state of the surface layer of the of heterogeneous materials properties solve direct and inverse problems of calculation of free oscillations in special samples with a layered structure. Design/methodology/approach. Theoretical-experimental technique for studying oscillations layered rods depending on the elastic moduli of forms and decrement each layer. The results of solving the inverse problem of determining the input parameters and technological conditions for the given experimental characteristics of the finished product. The character of the influence of the elastic modulus of the surface layer of the scattering parameters of the mechanical energy of homogeneous material with different mechanical characteristics. Findings. A calculation of the dissipation of mechanical energy with a homogeneous material but different mechanical characteristics, which can be considered as a system with three or more layers. The solution of this direct problem made it possible to solve the inverses problem – for a given operating parameters necessary to determine the technological regimes and initial physical and mechanical parameters of the material from which made the finished part. Originality/value. Based on the decisions of the direct problem is solved the inverse problem of determining the input mechanical characteristics of the material for a given initial operating parameters.
Energy dissipation during vibration of inhomogeneous materials with mechanical properties and direct and inverse problems when calculating vibrations layered structuresdy
Keywords: розсіяння механічної енергії; логарифмічний декремент коливання; обернена задача; mechanical energy dissipation; logarithmic decrement; the inverse problem